High Performance UHF RFID Tags for Item Level Tracing Systems in Critical Supply Chains - Catarinucci, Luca; Colella, Riccardo; Blasi, Mario De; Patrono, Luigi; Tarricone, Luciano (IntechOpen, 2011)
None